Fat-Associated Lymphoid Clusters in Inflammation and Immunity - Cruz-Migoni, Sara; Caamaño, Jorge (Frontiers in Immunology, 2016)
Fat associated lymphoid clusters are atypical lymphoid tissues that were originally identified in mouse and human mesenteries due to that they contain a high number of Type 2 Innate Lymphoid cells/Nuocytes/Natural Helper cells. FALCs are located on adipose tissues (AT) in mucosal surfaces such as the mediastinum, pericardium, and gonadal fat. Importantly these clusters contain B1, B2 cells and T lymphocytes as well as myeloid and other innate immune cell populations. The developmental cues of FALC formation have started to emerge, showing that these clusters depend on a different set of molecules and cells than secondary lymphoid tissues for their formation. Here we review the current knowledge on FALC formation and we compare FALCs and omental milky spots and their responses to inflammation.